2015
DOI: 10.5212/publicatioci.soc.v.23i2.0002
|View full text |Cite
|
Sign up to set email alerts
|

Assédio Moral nas Organizações: Impactos e o Papel dos Profissionais de Recursos Humanos.

Abstract: Este ensaio teórico objetiva promover reflexões sobre o assédio moral nas organizações e discutir a posição dos profissionais de Recursos Humanos. Busca compreender o assédio moral conceitualmente, contextualizado no sistema macro socioeconômico, além de analisá-lo à luz dos processos de Recursos Humanos. Subliminarmente, ressalta a importância estratégica da área de Recursos Humanos nas organizações, e também apresenta críticas sobre as práticas de gestão quando se mostram inadequadas. Entre as conclusões, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
(7 reference statements)
0
0
0
Order By: Relevance
“…This paper contributes on both the organizational and academic level, as studies about moral harassment are relatively new, as pointed out by Lage and Emmendoerfer (2010), Lorentz, Lima, and Maestro Filho (2011), Nunes (2011) and Rodrigues (2010). This study fills the gaps identified by Lima, Bispo, Gonçalves and Coelho (2014), who indicate the need to broaden understanding about the subject, focusing on both the harassed employee´s discourses and other aspects surrounding the phenomenon.…”
Section: Introductionmentioning
confidence: 95%
“…This paper contributes on both the organizational and academic level, as studies about moral harassment are relatively new, as pointed out by Lage and Emmendoerfer (2010), Lorentz, Lima, and Maestro Filho (2011), Nunes (2011) and Rodrigues (2010). This study fills the gaps identified by Lima, Bispo, Gonçalves and Coelho (2014), who indicate the need to broaden understanding about the subject, focusing on both the harassed employee´s discourses and other aspects surrounding the phenomenon.…”
Section: Introductionmentioning
confidence: 95%